Identification of Immune Responses to Japanese Encephalitis Virus Specific T Cell Epitopes - Pushpakumara, Pradeep Darshana; Jeewandara, Chandima; Wijesinghe, Ayesha; Gomes, Laksiri; Ogg, Graham S.; Goonasekara, Charitha Lakshini; Malavige, Gathsaurie Neelika (Frontiers in Public Health, 2020)
Background: Due to the similarity between the dengue (DENV) and the Japanese encephalitis virus (JEV) there is potential for immune cross-reaction. We sought to identify T cell epitopes that are specific to JEV and do not cross react with DENV. Methodology: 20mer peptides were synthesized from regions which showed >90% conservation. Using IFNγ cultured ELISpot assays, we investigated JEV-specific T cell responses in DENV- and JEV- non-immune individuals (DENV-JEV- =21), JEV seronegative and had not received the JE vaccine, but who were DENV seropositive (DENV+JEV- =22), JEV+(seropositive for JEV and had received the JE vaccine), but seronegative for DENV (DENV-JEV+ =23). We further assessed the responses to these peptides by undertaking ex vivo IFNγ assays and flow cytometry. Results: None of DENV-JEV- individuals responded to any of the 20 JEV-specific peptides. High frequency of responses was seen to 6/20 peptides by individuals who were JEV+ but DENV-, where over 75% of the individuals responded to at least one peptide. P34 was the most immunogenic peptide, recognized by 20/23 (86.9%) individuals who were DENV-JEV+, followed by peptide 3 and peptide 7 recognized by 19/23 (82.6%). Peptide 34 from the NS2a region, showed less than 25% homology with any flaviviruses, and <20% homology with any DENV serotype. Peptide 20 and 32, which were also from the non-structural protein regions, showed <25% homology with DENV. Ex vivo responses to these peptides were less frequent, with only 40% of individuals responding to peptide 34 and 16-28% to other peptides, probably as 5/6 peptides were recognised by CD4+ T cells. Discussion: We identified six highly conserved, T cell epitopes which are highly specific for JEV, in the Sri Lankan population. Since both JEV and DENV co-circulate in the same regions and since both JE and dengue vaccines are likely to be co-administered in the same geographical regions in future, these JEV-specific T cell epitopes would be useful to study JEV- specific T cell responses, in order to further understand how DENV and JEV-specific cellular immune responses influence each other.